CHARACTERISATION OF SOFT MAGNETIC COMPOSITES - Neethirajan,Rajesh Krishnan (2025)
Soft Magnetic Composites (SMCs) represent a new generation of materials gaining attention for their effective use in electric motors and transformers. The strong magnetic properties, reduced eddy current losses, and flexibility in forming complex 3D shapes. They offer clear advantages over traditional laminated steels, especially in the designs where magnetic behavior is needed in all directions. SMCs are made from iron particles coated with an insulating layer, offer a unique combination of design flexibility and functional efficiency, making them well-suited for complex electromagnetic applications. This study focuses on exploring the microstructure and porosity of SMCs, aiming to better understand and improve their role in electromagnetic systems, particularly in motor component applications. The analysis of SMC materials fabricated through conventional die compaction methods, using high-purity iron powder coated with insulating layers. Samples were subjected to systematic surface preparation and examined using digital optical microscopy combined with image processing techniques in ImageJ. Quantitative parameters such as particle size, coating area, and pore equivalent diameter were extracted from nine distinct regions across the samples. The results reveal significant Variation across regions. This non-uniformity affects the electromagnetic properties of SMCs but also suggests unequal pressure distribution during compaction. These findings provide valuable insight into optimizing compaction parameters and improving the homogeneity and functional performance of soft magnetic materials.
Keywords: SOFT MAGNETIC COMPOSITES